Older People and Social Connectedness: How Place and Activities Keep People Engaged - Irene H. Yen; Janet K. Shim; Airin D. Martinez; Judith C. Barker (Journal of Aging Research)
To understand how older adults perceive and navigate their neighborhoods, we examined the implications of activity in their neighborhoods for their health. We interviewed 38 adults (ages 62–85) who lived in San Francisco or Oakland, California. Seven key themes emerged: (1) people express a wide range of expectations for neighborliness, from “we do not bother each other” to “we have keys to each other’s houses”, (2) social distance between “other” people impede a sense of connection, (3) ethnic differences in living arrangements affect activities and activity locations, (4) people try to stay busy, (5) people able to leave their homes do many activities outside their immediate residential neighborhoods, (6) access to a car is a necessity for most, and (7) it is unusual to plan for the future when mobility might become limited. Multiple locations influence older adults’ health, including residential neighborhoods. Older adults value mobility, active lives, and social connections.